Identifying the prevalence of destructive leadership behavior and its determinants in northwest Ethiopia - Eshetu Mebratie; Birhanu Shanbel (Cogent Business & Management, 2024)
Destructive leadership behaviors and their effects on the organization have received little attention in terms of research & theory development. As a result, the purpose of this article is to investigate the prevalence and determinants of destructive leadership behavior from the quantitative data collected through questionnaire. A total of 947 sample employees were included in this study stratified sampling technique. Personal behavior, ineffective decision, management incompetency, and political behavior have a positive significance difference at p = 0.01 after the data has been analyzed through factor analysis and regression analysis. However, at the 1% significance level, the difference in political behavior and negotiation problem is negative. On the other hand, poor communication has a negative relationship with destructive leadership behavior, but it is statistically insignificant at a 5% alpha level. According to the findings, ∼65% of public-sector employees in the Awi zone are susceptible to destructive leadership. In this case, the researchers recommended that organizations intentionally and consistently need to promote an environment in which employees feel free to speak up about leaders' behavior that they believe it violates not only their own but also the organization's values.For the success of any organization, good leaders are needed; but a mere focus on those good leadership traits is not enough to get the organization more effective and efficient. So, this study is intended to show the prevalence of destructive eadership and contributing factors in target public organizations. It is founded that Leaders may behave destructively for a variety of reasons, be it their personality, incompetence, inability to negotiate, perceived injustice or threat to their identity, ineffective decision-making, financial reasons, low organizational identification, Political behavior etc.
Keywords: 650; Destructive leadership; multiple regression; leadership behavior; factor analysis; determinants